2017
DOI: 10.1111/jiec.12647
|View full text |Cite
|
Sign up to set email alerts
|

LEED v4: Where Are We Now? Critical Assessment through the LCA of an Office Building Using a Low Impact Energy Consumption Mix

Abstract: Various green building rating systems (GBRSs) have been proposed to reduce the environmental impact of buildings. However, these GBRSs, such as Leadership in Energy and Environmental Design (LEED) v4, are primarily oriented toward a building's use stage energy consumption. Their application in contexts involving a high share of renewable energy, and hence a low-impact electricity mix, can result in undesirable side effects. This paper aims to investigate such effects, based on an existing office building in Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…The results showed that embodied, operational, and transport energy represented 40%, 33% and 27%, respectively, of the total energy used. Lessard et al [ 26 ] showed that building life cycle analysis (LCA) results indicated the contribution of materials to environmental impact was >50% for the Quebec region in Canada, where more than 95% of the electricity is renewable. In addition, for the Ontario region (Canada), the contribution of energy consumption energy was 90% due to electricity generated from nuclear power.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that embodied, operational, and transport energy represented 40%, 33% and 27%, respectively, of the total energy used. Lessard et al [ 26 ] showed that building life cycle analysis (LCA) results indicated the contribution of materials to environmental impact was >50% for the Quebec region in Canada, where more than 95% of the electricity is renewable. In addition, for the Ontario region (Canada), the contribution of energy consumption energy was 90% due to electricity generated from nuclear power.…”
Section: Introductionmentioning
confidence: 99%
“…Embodied energy can reach up to 46% of a building's total energy consumption [13]. In contexts where the operational energy is produced from low-carbon sources, the embodied energy of construction materials is of greater importance, and can represent more than 50% of total impacts in some cases [14]. This impact shift highlights the importance of building materials, which must be addressed to maximize the climate change mitigation potential of the building sector [15].…”
Section: Of 30mentioning
confidence: 99%
“…Sartori and Hestnes (2007) showed that design of low-energy buildings is beneficial for life cycle energy demand but increases the embodied energy. In contexts involving high share of renewable energy, Lessard et al (2017) have concluded via an exhaustive LCA that contributions from materials can account for more than 50% for the environmental impact, the other part coming from the energy consumption (Lessard et al 2017). Therefore, there is a great need to optimize building designs according to these two objectives (i.e.…”
Section: Case Studymentioning
confidence: 99%